THE IMPACT OF REWARDS AND PUNISHMENTS ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORK MOTIVATION - Norawati, Suarni; Rifa Zahera (JURNAL ILMIAH EDUNOMIKA, 2025)
Employee performance is a requirement for every company, including employees at PT RIM Syam Gold Bangkinang. The important thing to note is the factors that influence employee performance. This study aims to determine and analyze the effect of rewards and punishment on employee work motivation, as well as the direct impact of rewards, motivation, and punishment on employee performance, and also the effect through employee work motivation as a mediator. Data was obtained using questionnaires with a total of 43 respondents. The data analysis uses the Structural Equation Model (SEM) and SmartPLS. The results reveal the rewards and punishments proven to have a positive and significant effect on employee work motivation. The main findings show that reward and punishment have an indirect significant effect on employee performance through employee work motivation. that employee work motivation can mediate the influence of punishment on employee performance. This study gives evidence that the implementation of appropriate punishment can increase employee work motivation, and employees who are well motivated will be able to work optimally, therefore that the results of the employee's work or performance can be maximized. Keywords: Reward; Punishment; Work Motivation: Employee Performance